Development of a Collaborative Learning-based Teacher Pedagogical Support Model at Vocational High Schools in Palembang: Needs Analysis - Afriany, Dina; Japar, Muhammad; Khaerudin, Khaerudin (PPSDP International Journal of Education, 2025)
The business and industrial sectors increasingly require Vocational High School (SMK) graduates to possess not only strong hard skills but also advanced soft skills. These competencies can only be developed through innovative and contextual learning practices. Many vocational teachers do not create tailored teaching materials that align with the curriculum, meet the needs of the business sector, and consider the characteristics of their students. To address these challenges, the involvement of learning support teacher, particularly School Supervisors and School Principals, is crucial in enhancing the quality of learning in schools. However, there is currently no structured support model that specifically addresses teachers’ practices, and School Supervisors are not sufficiently engaged as coaching partners within the schools. From interviews, observations, and a survey of a random sample of 51 teachers from 147 vocational non-educational teachers in Palembang City, the average pedagogical understanding was 55.75, hence immediate measures are needed to address teachers with low pedagogical competence. Considering the varying expertise of each school assistant, the collaboration of learning that combines training and guidance with mentoring and optimises individual and group competencies by providing support in the form of coaching is currently the appropriate strategy.